THE FORMATION OF VITAMIN C FUND IN SWEET CHERRY FRUITS UNDER THE EFFECT OF WEATHER FACTORS - Ivanova, I. Ye.; Serdyuk, M. Ye.; Тymoshchuk, Т. M.; Marenych, M. M. (Scientific Progress & Innovations, 2021)
Vitamin C is one of the most widely spread natural anti-oxidants which can be found in sweet cherry fruits. Nowadays there is great interest to biologically active compounds of stone fruits. It necessitates the selection of not only the crops but also separate varieties with a higher content of vitamin C. The accumulation of vitamin C in sweet cherry fruits depends on the variety as well as weather conditions. In this connection, the purpose of the research was to give scientific substantiation to the rate of stress weather factors’ impact and variety features on the process of vitamin C fund formation in sweet cherry fruits during the period of 2008–2019. The berries of 33 sweet cherry varieties of three terms of ripening, which were grown on fruits farms of the Southern region of Ukraine, were chosen for studying. It has been established, that among the varieties of an early term of ripening, Kazka and Zabuta varieties were characterized by a medium content of vitamin C (7.36 mg/100 g and 7.31 mg/100 g, respectively). Bigaro Burlat (Vр=17.9 %) was selected with regard to a minimal variation of the value during the years of research. According to vitamin C content and the variation of its formation, the most perspective from the technological point of view were the varieties of medium and late terms of ripening – Kordia (10.63 mg/100 g under Vр=17.1 %), Mirazh (10.67 mg/100 g under Vр=14.0 %). It has been proved, that during the period of research, weather conditions had dominating effects on the formation of vitamin C fund in an early and late groups of varieties. As for the groups of the varieties of a medium term of ripening, the accumulation of vitamin C depended more on the variety features. Taking into account the obtained results of a two-factor dispersion analysis, it is expedient to forecast the vitamin C content in the sweet cherry fruits of an early and a late term of ripening with regards to the average values, but not separately for each pomological variety.